Calcium Silicate Recommendations for Sugarcane on Florida Mineral Soils - J. Mabry McCray (EDIS, 2022)
The publication presents recommendations for calcium silicate application for sugarcane grown on Florida mineral soils along with supporting information. Written by J. Mabry McCray, and published by the UF/IFAS Agronomy Department, August 2022.